Extension approaches to rice integrated pest management in the Philippines - Velasco, Luis Rey I. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 1999)
The conceptual framework and field impact of the farmer field school (FFS) approach and the farmer participatory research (FPR) approach to integrated pest management (IPM) extension in the Philippines were reviewed. Published reports indicated the significant impact of the two participatory approaches in improving farmers' pest management decision making and practices, at least, in terms of reduction in pesticide use without significant yield reduction. Available published field data, however, were insufficient to critically examine the soundness of the conceptual frameworks of the two approaches and their underlying assumptions particularly in the context of farmer education.